Prevalence and risk factors of carbapenem-resistant Enterobacterales positivity by active screening in intensive care units in the Henan Province of China: A multi-center cross-sectional study - Guo, Bo; Guo, Ziqi; Zhang, Huifeng; Shi, Chuanchuan; Qin, Bingyu; Wang, Shanmei; Chang, Yinjiang; Chen, Jian; Chen, Peili; Guo, Limin; Guo, Weidong; Han, Huaibin; et al. (Frontiers in Microbiology, 2022)
Objective In intensive care units (ICUs), carbapenem-resistant Enterobacterales (CRE) pose a significant threat. We aimed to examine the distribution, epidemiological characteristics, and risk factors for CRE positivity in ICUs. Materials and methods This cross-sectional study was conducted in 96 ICUs of 78 hospitals in Henan Province, China. The clinical and microbiological data were collected. A multivariable logistic regression model was used to analyze the risk factors for CRE positivity. Results A total of 1,009 patients were enrolled. There was a significant difference in CRE positive rate between pharyngeal and anal swabs (15.16 vs. 19.13%, P < 0.001). A total of 297 carbapenem-resistant Klebsiella pneumoniae (CR-KPN), 22 carbapenem-resistant Escherichia coli (CR-ECO), 6 carbapenem-resistant Enterobacter cloacae (CR-ECL), 19 CR-KPN/CR-ECO, and 2 CR-KPN/CR-ECL were detected. Klebsiella pneumoniae carbapenemase (KPC), New Delhi metallo-beta-lactamase (NDM), and a combination of KPC and NDM were detected in 150, 9, and 11 swab samples, respectively. Multivariable logistic regression analysis determined length of ICU stay, chronic neurological disease, transfer from other hospitals, previous infection, and history of antibiotics exposure as independent risk factors for CRE positivity. Age and cardiovascular diseases were independent risk factors for mixed infections of CRE. The occurrence of CRE in secondary and tertiary hospitals was 15.06 and 25.62%, respectively (P < 0.05). Patients from tertiary hospitals had different clinical features compared with those from secondary hospitals, including longer hospital stays, a higher rate of patients transferred from other hospitals, receiving renal replacement therapy, exposure to immunosuppressive drugs, use of antibiotics, and a higher rate of the previous infection. Conclusion In ICUs in Henan Province, CRE positive rate was very high, mostly KPC-type CR-KPN. Patients with prolonged ICU stay, chronic neurological disease, transfer from other hospitals, previous infection, and history of antibiotic exposure are prone to CRE. Age and cardiovascular diseases are susceptibility factors for mixed infections of CRE. The CRE positive rate in tertiary hospitals was higher than that in secondary hospitals, which may be related to the source of patients, antibiotic exposure, disease severity, and previous infection.